2004
DOI: 10.1097/01.prs.0000095942.71618.9d
|View full text |Cite
|
Sign up to set email alerts
|

New Murine Model of Spontaneous Autologous Tissue Engineering, Combining an Arteriovenous Pedicle with Matrix Materials

Abstract: The authors previously described a model of tissue engineering in rats that involves the insertion of a vascular pedicle and matrix material into a semirigid closed chamber, which is buried subcutaneously. The purpose of this study was to develop a comparable model in mice, which could enable genetic mutants to be used to more extensively study the mechanisms of the angiogenesis, matrix production, and cellular migration and differentiation that occur in these models. A model that involves placing a split sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
130
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(134 citation statements)
references
References 23 publications
4
130
0
Order By: Relevance
“…23 Here the cells grow in parallel with the newly developing capillary bed to form a vascularized interconnected network of cardiac tissue. We have previously shown in both rat 21 and mouse 38 chambers that other implanted tissues and cells, such as muscle, 17 myoblasts, 17 fat, 39 pancreatic islets, 40 fetal tissue, and fibroblasts, 16 can survive with this methodology. By seeding cardiomyocytes into a chamber in the rat, we have grown a living piece of cardiac tissue with a volume of Ϸ0.2 mL and thickness up to 1983 m, which easily exceeds the dimensions expected to be supported by diffusion alone (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…23 Here the cells grow in parallel with the newly developing capillary bed to form a vascularized interconnected network of cardiac tissue. We have previously shown in both rat 21 and mouse 38 chambers that other implanted tissues and cells, such as muscle, 17 myoblasts, 17 fat, 39 pancreatic islets, 40 fetal tissue, and fibroblasts, 16 can survive with this methodology. By seeding cardiomyocytes into a chamber in the rat, we have grown a living piece of cardiac tissue with a volume of Ϸ0.2 mL and thickness up to 1983 m, which easily exceeds the dimensions expected to be supported by diffusion alone (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Cylindrical silicone chambers, 5 mm long, 3.35 mm internal diameter, 44 l volume (Dow-Corning Corp., Midland, MI) were placed on the right epigastric pedicle according to a method modified from Cronin and colleagues 22 ( Figure 1, a-d). The right superficial epigastric vessels were dissected free of surrounding tissue from their origin at the femoral vessels to their insertion into the groin fat pad.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…[3][4][5][6] We have developed a murine tissue engineering model that comprises a silicon chamber enclosing the superficial epigastric vascular pedicle in a Matrigel environment. The chamber has been used in several formats, closed, 7 partially closed 8 , and in a delayed seeding model. 9 We have demonstrated that new vascularized tissue forms in the chamber 7 and that an open chamber, allowing contact with surrounding tissue, improves adipogenesis.…”
Section: Introductionmentioning
confidence: 99%